Manual para organização e destinação de massa documental acumulada no Departamento de Patologia da UFRN - Araújo, Gislaine Maria da Costa Leôncio de (2024)
The concept of information is broad and covers several areas of knowledge. The growing use of information is directly linked to the complexity of organizational environments, being essential for their functioning. The objective of this work is to carry out a study to produce an organization manual for the Accumulated Document Mass in the Department of Pathology at the Federal University of Rio Grande do Norte (UFRN). The choice of this theme came from the motivation to bring improvements to the UFRN Pathology Department, aiming at the quality of daily activities carried out in the sector, bringing security and organization to this documentation. The importance of health files is highlighted, especially medical pathological reports, for the diagnosis and treatment of diseases. However, the disorderly accumulation of documents compromises the efficiency of routine activities, making access to information difficult and increasing operational costs. The work is characterized as basic research, which seeks to understand concepts of information management and document management. As for the methodology, bibliographical research was carried out in several databases and resulted in the preparation of a manual for organizing and disposing of the Accumulated Document Mass. This work offers a technical product that can assist employees in the sector